(untitled) (Scientific Journal for Publishing in Health Research and Technology, 2025)
The integration of virtual laboratories (VLABs) into biophysics education addresses critical resource constraints while introducing pedagogical trade-offs. This mixed-methods study evaluates 412 undergraduate biophysics students across three universities, comparing learning outcomes between virtual, physical, and blended laboratory formats. Quantitative analysis revealed VLAB cohorts demonstrated significantly higher conceptual understanding in molecular dynamics (Δ+1.32 SD, p=0.007) but scored lower in experimental troubleshooting (Cohen’s d = 1.24, p<0.001). Qualitative data from 37 instructor interviews identified persistent limitations in simulating stochastic single-molecule phenomena. Thematic analysis of student reflections highlighted accessibility benefits for diverse learners but reduced collaborative engagement. We propose an evidence-based blended framework optimizing cost-efficiency while preserving essential tactile experiences in biophysics education.